Man Ra’ani fi al-Manam Fasayari fi al-Yaqdhah: The Reality of Dream in Syaikh ‘Abd Qadir al-Jaylany’s Hadits Intrepretation within his Sirr al-Asrar - AB, Zuherni (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
Man Ra’ani fi al-Manam Fasayarani fi al-Yaqdhah was the popular hadits examined the blessed for those who sees the Prophet PBUH in a dream, indeed will see him while awake. It’s seems likewise a clue that each person in each generation blessed the same experience with whom saw him in his life relatively. In addition, this hadits prevalently discuss in Sufism writings and literatures. One of them is Sirr al-Asrar wa Madhhar al-Anwar a masterpiece work written by Shaikh ‘Abd al-Qadir al-Jaylany. This research exercise to find the examination of Shaikh ‘Abd al-Qadir toward the hadits from Sufis tradition approach. Chapter twenty second in Sirr al-Asrar elaborated in detail the evidence proven of dream and waking fullness. Syaikh ‘Abd Qadir al-Jaylani recorded from various hadits that the truthfull dream obviously one of indication of prophetic. He affirmed the limitations belong to the truthfull dream (ru’yat al-shalihat) experienced esotericly by each inner faculties such as al-qalb, al-nafs and al-ruh throught precious vision. Instead the experience also symbolized lower character in particular despicable visions. This kind of method applied for truthull reality restrictly.